Optimization of Alternative Assessment with Modified MOORA Method: Case Study of Contract Employee Selection - Waqas Arshad, Muhammad; Sintaro, Sanriomi; Rahmanto, Yuri; Wantoro, Agus; Setiawansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Multi-Objective Optimization by Ratio Analysis (MOORA) is a multi-criteria decision-making method used to evaluate and select the best alternative based on multiple objectives or criteria. One of the main disadvantages of the MOORA method is subjectivity in the determination of the weight of criteria. In this method, the decision maker must determine the relative weight of each criterion used to evaluate alternatives. Subjectivity in the weighting of criteria can also lead to inconsistencies between different decision makers or experts, resulting decisions can be less transparent and less acceptable to all parties involved, reducing confidence in the validity and accuracy of the results. Optimization of alternative assessment with modified MOORA method is to develop alternative assessment methods that are more accurate and objective by integrating standard deviation into the MOORA method. This study aims to overcome the weaknesses of conventional MOORA methods in dealing with data variation and assessment subjectivity by introducing a more data-driven mechanism of calculating the weight of criteria. Through testing and comparing performance between modified MOORA methods and conventional methods, this study aims to demonstrate improved accuracy, consistency, and reliability in alternative assessment results. In addition, this research is expected to provide practical implementation guidance for the application of the modified MOORA method in the Decision Support System (DSS), so as to improve the efficiency and quality of decision making in various sectors. The ranking results showed that the results of rank 1 were obtained by Employee 6 with a final score of 0.3375, rank 2 was obtained by Employee 3 with a final score of 0.2904, and rank 3 was obtained by Employee 7 with a final score of 0.2756. The results of the comparison test of the original rank with SD-MOORA showed a correlation value of 1, so it can be concluded that there is a very strong and positive relationship between the original rating and the SD-MOORA rating. This shows that the rating produced by SD-MOORA is very consistent with the original ranking, thus giving validity to the effectiveness of SD-MOORA in replicating the original rating results more objectively and efficiently. The results of the SD-MOORA modification showed significant improvements in the accuracy and objectivity of decision making.